DESCRIPTION OF RECIPE COMPLETENESS IN TAMBUSAI UTARA II HEALTH CENTER, TAMBUSAI UTARA DISTRICT, ROKAN HULU DISTRICT, 2020 - Hanindiya, Beta; Dingel, Jonathan; Kurniawan, Hendri; Mustaruddin, Mustaruddin; Sanjaya, Muhartri (Universitas Efarina, 2021)
Doctors carry out their duties as health service providers, doctors will not be separated from things called prescriptions. Prescription is the final embodiment of physician competence in medical care. A good prescription should contain enough information to enable the pharmacist concerned to understand what drug is to be given to the patient. The aim was to find out the completeness of prescriptions at the Petatal Health Center in accordance with PMK No. 74 of 2016. The research was descriptive in nature, with random data collection and observing incoming recipes during the January-December 2018 period written by doctors. Administrative screening was carried out on 384 doctor's prescriptions by filling in the data collection table, according to the completeness aspect of the prescription being reviewed.